Leadership questions and effective trade union functions (2023)
Trade union is important to effective industrial relationship in any economy. Organisations exist to create labour productivity and wealth in the economy but the sustenance of the objective in a competitive environment is moderated by the trade union and how its functions are managed by its leadership complex and competitive environment. Rather than harmonious relations that should foster productivity, trade disputes and strikes have been commonplace with consequences on the economy. The Nigerian Labour Congress (NLC), Academic Staff Union of Universities (ASUU), NASU, and Nigerian Medical Association (NMA) and others have been involved in prolonged industrial disputes with their employers and the government at various times in the last two years. The incessant industrial disputes have shifted attention of scholars and other stakeholders to the functions of the trade union particularly the capacity of its leadership to effectively manage the activities of the trade union and redirect the union to the path of value creation and functional relationship with the employers and government. This paper will focus on questions that workers ask in the workplace about their career and future as it relates to their associations and the meaning they derive from the response they get from leadership.